2013
DOI: 10.4103/1793-5482.116386
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic spinal cord herniation: Clinical review and report of three cases

Abstract: Idiopathic spinal cord herniation (ISCH) is a rare condition, of unknown pathogenesis, that primarily affects the thoracic spinal cord. It is characterized by ventral displacement of the spinal cord through a dural defect. The aim of this study was to review the literature and to present a retrospective single center experience with three cases of ISCH. The literature review analyzed a total of 78 relevant publications on ISCH, which included a total of 171 patients, supplemented with 3 patients treated at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 66 publications
1
40
0
4
Order By: Relevance
“…ISCH is a recognised cause of progressive myelopathy with reported incidence of <200 cases, almost exclusively involving the thoracic spine 3. It most commonly presents as Brown-Sequard syndrome 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISCH is a recognised cause of progressive myelopathy with reported incidence of <200 cases, almost exclusively involving the thoracic spine 3. It most commonly presents as Brown-Sequard syndrome 4.…”
Section: Discussionmentioning
confidence: 99%
“…This condition was first described in 1974 by Wortzman et al 1. Around 170 cases of ISCH have been described in the literature, and all these lesions were found in the thoracic spine with the majority between the T2 and T8 vertebrae 2 3…”
Section: Introductionmentioning
confidence: 99%
“…8,10 In a series of 12 patients with spinal cord herniation, 50% of the patients attained postoperative clinical improvement; however, a more recent review of 159 cases in the literature suggested a symptom improvement rate of 74% of patients. 12 Although the majority of studies have reported favorable outcomes in patients with spinal cord herniation syndromes, long-term follow-up of surgically managed patients is warranted to assess postoperative course and complications such as the recurrence of ventral cord tethering, concentric scarring, and cord swelling, which have been documented in a number of studies. 1 In cases where the condition is not clinically or radiologically progressive, conservative management has been encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…1 Presently, no evidence-based guidelines on the optimal treatment modalities for spinal cord herniation exist, and patient management has been largely individualized. 12 Although the majority of patients are treated with surgical measures, precise predictive algorithms to identify patients who would benefit from surgery are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation